Combined medial patellofemoral and patellotibial reconstruction with soft tissue fixation in recurrent patellar dislocation. Issue 8 (August 2020) - Maffulli, Nicola; Aicale, Rocco; D'Addona, Alessio; Young, David A; Kader, Deiary F; Oliva, Francesco
Highlights: The medial patellofemoral ligament (MPFL) is the primary passive restraint to lateral patellar translation at 0° to 30° of knee flexion, while, the medial patellotibial ligament (MPTL) and medial patellomeniscal ligament (MPML) are considered secondary restrains of patellar stability. However, MPTL has different biomechanical properties compared to the MPFL, which is less stiff than the former. 27 males and 7 females with a mean age of 26.5 ± 10.7 years (range, 13–39 years) were evalued. With a mean follow-up was 3.1 years (range, 2.5–4 years) the mean modified Cincinnati score and Kujala scores increased with no significant differences between patients with or without osteochondral lesions and between male and female patients ( P ≥ .05). Combined reconstruction of MPFL and MPTL using an ipsilateral autologous gracilis tendon is satisfactory and effective and can be considered as suitable management option to treat recurrent dislocation of the patella. Abstract: Introduction: The medial patellofemoral and patellotibial ligaments (MPFL and MPTL) are the main passive restraints to lateral patellar translation. When nonoperative management of patellofemoral dislocations fails, surgical options can be considered to restore patellofemoral stability. Several reconstruction procedures of the MPFL with semitendinosus, gracilis, quadriceps tendon, and synthetic grafts have been described. No clear superiority of one surgical technique over another is evident. Materials and methods: Patients who suffered at least two documented episodes of unilateral patellar dislocation, confirmed radiographically and at clinical examination, underwent combined MPFL and MPTL reconstruction. Patients were regularly followed-up postoperatively at 2, 4, 8, 12, and 24 weeks, and then annually for a minimum of 2.5 years. Clinical and functional evaluations were performed using the modified Cincinnati rating system and the Kujala score, while anthropometry values including thigh volume and cross-sectional area of the thigh were measured before the operation and at the latest follow-up bilaterally. Results: There were 7 males and 27 females with a mean age of 26.5 ± 10.7 years (range, 13–39 years). The mean follow-up was 3.1 years (range, 2.5–4 years). The mean modified Cincinnati score Increased from 51 ± 22 preoperatively to 90 ± 19 ( P = .001). The mean Kujala scores increased from 47 ± 17 preoperatively to 82 ± 17 ( P = .02), with no significant differences between patients with or without osteochondral lesions ( P ≥ .05), and between male and female patients ( P ≥ .08). The Insall-Salvati index was 1.1 preoperatively and remained within normal range ( P = .05) at the latest follow-up. Conclusion: Combined reconstruction of MPFL and MPTL using an ipsilateral autologous gracilis tendon is satisfactory and effective and can be considered as suitable management option to treat recurrent dislocation of the patella. However, randomized studies are needed to compare different techniques. Study design: Case series.